Análise da influência de superfícies refletivas nas perdas de calor de sistema térmicos - Cavalcanti, Marcos Alexandre de Vasconcelos (2011)
The use of reflective surfaces functioning as thermal insulator has grown significantly over the years. Reflective thermal insulator are materials that have several characteristics such as low emissivity, low absorptivity and high reflectivity in the infrared spectrum. The use of these materials has grown a lot lately, since it contains several important radioactive properties that minimize the heat loss of thermal systems and cooling systems that are used to block the heat on the roof of buildings. A system made of three surfaces of 316 stainless steel mirror was built to analyze the influence of reflective surfaces as a way to reduce the heat loss and thereby conserve the energy of a thermal system. The system was analyzed both with and without the presence of vacuum, and then compared with a system that contained glass wool between the stainless steel mirror walls, since this isolator is considered resistive and also broadly used around the world in thermal systems. The reflectivity and emissivity of the surfaces used were also measured in this experiment. A type K thermocouple was fixed on the wall of the system to obtain the temperature of the stainless steel mirror surfaces and to analyze the thermal behavior of each configuration used. The results showed an efficiency of 13% when the reflective surfaces were used to minimize the heat loss of the thermal system. However, the system with vacuum had the best outcome, a 60% efficiency. Both of these were compared to the system made of glass wool as a thermal insulator